Collegiate baseball pitchers demonstrate a relationship between ball velocity and elbow varus torque, both within and across pitchers - Sakurai, M.; Barrack, A. J.; Lobb, N. J.; Wee, C. P.; Diaz, P. R.; Michener, L. A.; Karduna, A. R. (Sports Biomechanics, 2023)
High elbow varus torque during baseball pitching has been identified as a potential cause of ulnar collateral ligament injury in baseball pitchers. In general, elbow varus torque increases as ball velocity increases across pitchers. However, studies incorporating within-subject analyses report that not all professional pitchers have a positive relationship between elbow varus torque and ball velocity (T-V relationship). It remains unknown whether collegiate pitchers show the same trend as professionals in their T-V relationships. The current study investigated the T-V relationship of collegiate pitchers focusing on both across and within pitchers. Division 1 collegiate pitchers (n = 81) were assessed for elbow torque and ball velocity during pitching. Both across- and within-pitcher T-V relationships were significant (p < 0.05) using linear regression. However, more variance in elbow varus torque was explained using the within-pitcher relationship (R2 = 0.29) than the across-pitcher relationship (R2 = 0.05). Of the 81 pitchers, nearly half (n = 39) had significant T-V relationships, while the other half (n = 42) did not. Our findings indicate that the T-V relationship should be assessed on an individual basis as T-V is pitcher-specific.